The Impact of Fiscal Policy on Addressing Economic Inequality in Jayapura City, 2014-2023 - Debora Dodop; Transna Putra Urip S; Stephanny Inagama Timisela; Lidiah Tereda Iwo; Syamsidar Sinaga; Dominggus Marey (AIBPM Publisher, 2025)
Economic inequality remains a persistent challenge in regional development, particularly in eastern Indonesia, including Jayapura City. This study aims to examine the impact of regional fiscal policy, specifically government expenditure on social programs, education, health, and infrastructure, on income inequality in Jayapura City during the period 2014–2023. The study employs a quantitative approach using multiple linear regression analysis based on secondary data obtained from the Regional Budget (APBD) and Statistics Indonesia (BPS). The results indicate that, simultaneously, the four categories of regional expenditure do not have a statistically significant effect on income inequality, although the regression model explains 62.2% of the variation in inequality. Partially, social expenditure shows a positive effect that approaches statistical significance, while expenditures on education, health, and infrastructure do not demonstrate a significant influence. These findings suggest that the effectiveness of regional fiscal spending in reducing income inequality in Jayapura City remains limited. Therefore, improvements in the quality of budget allocation, spending efficiency, and targeting accuracy are essential. This study provides important policy implications for local governments in formulating more inclusive and inequality-oriented fiscal strategies.